Competition, Technology and Market Shares - Shen, T. Y. (The Review of Economics and Statistics, 1968)
JN an earlier paper we have reported that manufacturing plants in two digit industries tend to cluster around an expansion path characterised by constant input output elasticities [4]. We have also argued that the nature of the path provides a motivation for the plants to grow, and this motivation has been further strengthened by the shifts of the path that took place. The question of differential rates of growth exhibited by the different plants still remains. Given an expansion path that excludes any optimal plant size, why should some plants exhibit a higher rate of growth than others? The question may be paraphrased in other ways. What determines a change in market share? 1 What is the source of competitive advantage enjoyed by some plants and not by others so that they grow at different rates? As we have shown elsewhere [5], part of the answer is in the nature of the expansion path and the relative position of the plants along the path. In this paper we will investigate whether the deviation of plants from the expansion path is also relevant in explaining their growth performance. The paper is in three sections. In the first section we analyze the duration of competitive advantage enjoyed by the plants. Where plants possess only a temporary competitive advantage randomly distributed among all the plants, a lognormal size distribution of plants ensues. On the other hand, where plants enjoy a persistent competitive advantage, the resulting systematic relationship between size and the rate of growth leads ultimately to a concentration of the market in the hands of a few large plants. The duration of competitive advantage depends on the source of competitive advantage. In the second section we focus on technology difference-measured by the different deviations of plant observations from the expansion path in a certain directionas a possible source. It is found that advanced technology contributes to the likelihood that a plant could maintain or expand its share of the market. However, superiority in technology of a given plant turns out to be generally transitory and appears to be related to the age of its machines and equipment. This suggests the hypothesis that, with technological progress, the natural life of machinery and equipment dominates the extent and the outcome of technology competition. Competition for market also comes from new entries. In the final section we find that new plants in an industry are characterized by greater capital intensity and therefore enjoy a competitive advantage at times of rising wages. In fact, the great significance of entry and exit indicates that the market share change is to a large extent related to the building of new plants and the abandoning of old plants. It is in this connection that technological progress and the change in the relative price of factors have the most significant impact on the competition for market.